An agile supply chain for a project-oriented steel product network - Iskanius, P. (Päivi) (University of Oulu, 2006)
Abstract Agility – namely, the ability of a supply chain to rapidly respond to changes in market and customer demands – is regarded as the bearer of competitive advantage in today's business world. The need for agility has traditionally been associated with supply chains in high technology industry products. However, traditional industries also face similar challenges in terms of speed, flexibility, increased product diversity and customization. This study contributes to the discussion on agility in supply chain management (SCM) and provides a novel focus on the development of an agile supply chain in a traditional industry.